How to make ECTS the "Easy Credit Transfer System" - Kreis, Oliver; Dieck, Jasmin; Nasarow, Alexander (International Conference on Recognition 2021 der Hochschulrektorenkonferenz HRK, 2021)
In this panel discussion, we will show how to design study programs and examination regulations ("Prüfungsordnungen") in advance to enable an easy recognition of courses taken abroad at the home university and to facilitate the individual recognition processes. This panel discussion focusses in engineering study programs, but the outcomes can also be transfered to other science areas. <br